The Effect of the Application of Teacher Teaching Styles on Swimming Learning Outcomes in PJOK Learning in Schools - Kambu, Alfince; Rahmat, Alit; Carsiwan, Carsiwan; Nugraha, Reshandi (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research is motivated by the lack of reading literacy skills among elementary school students. This is caused by the lack of adequate reading infrastructure, including libraries and limited variety of books. The purpose of this study is to find out how the use of the Let's Read application affects the reading literacy skills of 5th grade elementary school students. This study uses quantitative research with quasi-experimental methods. The design used in this study was a pre-experimental design where only one class was given a pre-test and a post-test, namely the experimental class without a control or comparison class. The questionnaire became the instrument used in this study. As for the respondents in this study were all 5th grade students, totaling 28 people. The treatment was given for 10 meetings. Data processing shows that the Let's Read application has a significant impact on the reading literacy skills of fifth grade students.